Prepaid And Postpaid Voice Over IP (VoIP) Architecture For Rural Areas - Ismail, Mohd Nazri (2007)
The aim of this study was to propose merging wireless technology in rural areas with wired technology in urban areas and the implementation of WAP technology that can provide value added services for prepaid and postpaid VoIP users.